(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
In the design of museums, through new technologies, a communicative connection with time is created, attracting the attention of visitors. The concept of museum design is also different in that it requires a unique creative approach. The study of the factors influencing the decisions of the interior design of the museum consists in the search and study of interior elements through technologies based on modernity, in accordance with the needs and interests of these institutions.